Inoculum prevalence, virulence, and morphometric variation of Phytophthora palmivora recovered from soil across cocoa plantations in East Luwu, Indonesia - EIRENE BRUGMAN; NUR HARDINA; TUTIK KUSWINANTI (Society for Indonesian Biodiversity, 2024)
Abstract. Brugman E, Hardina N, Kuswinanti T. 2024. Inoculum prevalence, virulence, and morphometric variation of Phytophthora palmivora recovered from soil across cocoa plantations in East Luwu, Indonesia. Biodiversitas 25: 4095-4104. In most cocoa plantations across Indonesia, the soilborne pathogen Phytophthora palmivora is a major concern for causing pod rot disease. This study aims to evaluate the inoculum prevalence, virulence, and morphological variation of P. palmivora in cocoa plantations across East Luwu. The pathogen was recovered from soil samples using the apple soil baiting method, and pure cultures were obtained on modified V8 juice agar media. Morphological observations included colony patterns and asexual features. Principal component analysis (PCA) was conducted to identify patterns in 12 measured morphometric variables. The virulence level was determined based on disease severity (%), latent period (days), and infection rate (day-unit?¹). Isolation via soil baiting confirmed the prevalence of P. palmivora in all soil samples (100%), confirming soil as a consistent source of inoculum in the cocoa plantation. Fifteen isolates exhibited varying sporangial shapes (ovoid, pyriform, and globose) and types (papillate, semi-papillate, and non-papillate), as well as globose intercalary and terminal chlamydospores with irregular collaroid, torulose, and loop hyphal swellings. The PCA plot grouped isolates into three clusters based on 12 morphometric variables, where all isolates from Mangkutana were included in the same cluster. The virulence test revealed that one isolate (KLN2) was avirulent, while the remaining isolates were pathogenic with low to medium virulence.